Legal Provisions and Restrictions on The Propagation of Non-Islamic Religions among Muslims in Malaysia - Zuliza Mohd Kusrin,; Zaini Nasohah,; Mohd al-Adib Samuri,; Mat Noor Mat Zain, (Kajian Malaysia, 2013)
Article 11 of the Federal Constitution of Malaysia states that every individual has the right to profess, practice and preach his religion or belief. However, Article 11(4) of the Federal Constitution also states that the propagation of non-Islamic religions among Muslims is forbidden. This article aims to discuss both the justifications and the legal restrictions – that is, the legal provisions – that restrict and control the propagation of non-Islamic religions among Muslims in Malaysia. This discussion identifies three justifications for the prohibition of the propagation of non-Muslim religions among Muslims in Malaysia. The first justification relates to the background and history of the special status and position of Islam in Malaya; the second relates to the key role of Malay Rulers in preserving the sanctity of the Islamic religion from the pre-independence period to the present day; and the third justification relates to the nature of Islamic teachings and the maxim that apostasy is a crime. Legal provisions that control the propagation of non-Islamic religions among Muslims are found at both federal and state levels. However, the problem of legal enforcement and, in particular, the jurisdictional limitations of the Syariah Courts over non-Muslims in Malaysia result in a lack of implementation of these legal provisions.